Analysis of e-Advertising Influence Case Study on Culinary Product - S Luckyardi; C N Albar; N N Supriatna (Journal of Business and Behavioural Entrepreneurship, 2021)
The purpose of this research is to analyse the influence of e-advertising on consumers. The case study was conducted on culinary product by performing literature study method and questionnaires. Purposive sampling technique was used with two criteria namely age and location of residence. The questionnaires was distributed among 100 respondents with age ranging from 18 to 24 years old and resided in Bandung. The results show that advertisement in social media or e-advertisements is effective to influence consumers, this is indicated by most of respondents stated that they know the product from social media, not only conventional media. In addition, the coverage of e-advertisement exposure is very extensive. This is also supported by the fact that young adults tend to use social media and other online platforms to find information regarding product. This research contribute recommendation to integrate online means in their advertisement method.